Lipid levels and major adverse cardiovascular events in patients initiated on statins for primary prevention: an international population- based cohort study protocol. Issue 1 (January 2021) - Blais, Joseph E; Coetzee, Annelize; Man, Kenneth KC; Beyene, Kebede A; Harrison, Jeff; Wong, Ian CK
No abstract available